Peningkatan Kepastian Hukum Melalui Pembentukan Produk Hukum Daerah yang Tertib, Terencana dan Terkoordinasi - Eki Furqon; Qotrun Nida (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The Pandeglang Regency, as defined by Law Number 12 of 2011 on the Formation of Legislation promulgated on August 12, 2011, plays a pivotal role in regional regulatory preparation. Law Number 12 of 2011 mandates technical regulations, in the form of government regulations and presidential regulations, to be developed around 2012. Regional Regulations (Raperda), as products of regional law, constitute a subset of statutory regulations. Positioned within the legal hierarchy under the Constitution, MPR Decrees, Laws/Government Regulations in lieu of Laws, and Presidential Regulations (Article 7, paragraph (1) of Law No. 12 of 2011), these regulations encompass legally binding norms. This paper employs a qualitative, normative juridical approach, involving the study and interpretation of legal literature and laws to address the issues at hand. Operationally, it relies on library research, delving into books, laws, and related documents. Focused on the return of evidence by the prosecutor, the study combines normative and empirical research for enhanced precision. Key findings include: 1) Raperda on Regional Legal Products serves as a guiding instrument for the formulation of regional legal products, fostering improved administrative arrangements and orderly documentation in Pandeglang Regency. 2) These regulations function as references derived from higher laws, establishing a framework for regional legal product creation. The study advocates for a comprehensive understanding of the legal hierarchy and underscores the significance of Raperda in shaping a well-organized administrative landscape in the Pandeglang Regency.